PERANCANGAN PUSAT PAGELARAN MUSIK DI TANGERANG SELATAN DENGAN PENERAPAN ARSITEKTUR TROPIS MODERN - Renaldy Ardiansyah; Sri Kurniasih; Dody Kurniawan (MAESTRO, 2022)
Tourism area is an activity that is developed in many areas to certain areas to attract the interest of the surrounding community. Especially art tourism, namely the art of music. To increase the love and passion for the art of music in a certain area, especially South Tangerang, it is necessary to have a music performance area, where there is a place for music education tours, musical performances, music culture, and local budget revenues. Music performances also have a good effect on the surrounding community, especially in South Tangerang because there is a place where music lovers and visitors can interact with each other. The modern tropical architectural approach can be used as a basic reference in the Central Design of music performances in South Tangerang. The concept of this building is very good to use, the shape of the building used can overcome the climatic conditions that exist in Indonesia by combining several things that have been adjusted, in order to complete the existing shortcomings.